Coding Variants in Nephrin (NPHS1) and Susceptibility to Nephropathy in African Americans - Bonomo, Jason A. (American Society of Nephrology, 2014)
BACKGROUND AND OBJECTIVES: Presumed genetic risk for diabetic and nondiabetic end stage renal disease is strong in African Americans. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: Exome sequencing data from African Americans with type 2 diabetic end stage renal disease and nondiabetic, non-nephropathy controls in the T2D-GENES study (Discovery, n=529 patients and n=535 controls) were evaluated, focusing on missense variants in NPHS1. Associated variants were then evaluated in independent type 2 diabetic end stage renal disease (Replication, n=1305 patients and n=760 controls), nondiabetic end stage renal disease (n=1705), and type 2 diabetes-only, non-nephropathy samples (n=503). All participants were recruited from dialysis facilities and internal medicine clinics across the southeastern United States from 1991 to present. Additional NPHS1 missense variants were identified from exome sequencing resources, genotyped, and sequence kernel association testing was then performed. RESULTS: Initial analysis identified rs35238405 (T233A; minor allele frequency=0.0096) as associated with type 2 diabetic end stage renal disease (adjustment for admixture P=0.042; adjustment for admixture+APOL1 P=0.080; odds ratio, 2.89 and 2.36, respectively); with replication in independent type 2 diabetic end stage renal disease samples (P=0.018; odds ratio, 4.30) and nondiabetic end stage renal disease samples (P=0.016; odds ratio, 4.48). In a combined analysis (all patients with end stage renal disease versus all controls), T233A was associated with all-cause end stage renal disease (P=0.0038; odds ratio, 2.82; n=3270 patients and n=1187 controls). A P-value of <0.001 was obtained after adjustment for admixture and APOL1 in sequence kernel association testing. Two additional variants (H800R and Y1174H) were nominally associated with protection from end stage renal disease (P=0.036; odds ratio, 0.44; P=0.0084; odds ratio, 0.040, respectively) in the locus-wide single-variant association tests. CONCLUSIONS: Coding variants in NPHS1 are associated with both risk for and protection from common forms of nephropathy in African Americans.